2021
DOI: 10.3390/ijerph182111719
|View full text |Cite
|
Sign up to set email alerts
|

Do Gender, Age, Body Mass and Height Influence Eye Biometrical Properties in Young Adults? A Pilot Study

Abstract: Background: Do gender, age, body mass and height influence eye biometrical properties in young adults? Methods: A total of 155 eyes (92 female, 63 male) of healthy subjects between the ages of 18 and 39 years were included in the study. The subjects’ gender and age were recorded, and their body mass, height and biometrical properties of the eyes were measured. Results: The male subjects had significantly thicker and flatter corneas and lower minimal rim-to-disk ratios than the female subjects did. In both gend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…Several studies have evaluated the factors affecting AL, reporting age, sex, and education level as the most important determinants [6,[24][25] . Evaluation of the relationship between sex and AL in the present study showed that AL was longer in men versus women (23.43 vs 23.01), which is consistent with previous studies where the longer AL in men has been attributed to their taller stature as well as physical differences between men and women [26][27][28] . Evaluation of the role of age in AL changes showed a decrease in AL with age in the study population, which was consistent with the majority of the previous studies [14,18,24] .…”
Section: Resultssupporting
confidence: 92%
“…Several studies have evaluated the factors affecting AL, reporting age, sex, and education level as the most important determinants [6,[24][25] . Evaluation of the relationship between sex and AL in the present study showed that AL was longer in men versus women (23.43 vs 23.01), which is consistent with previous studies where the longer AL in men has been attributed to their taller stature as well as physical differences between men and women [26][27][28] . Evaluation of the role of age in AL changes showed a decrease in AL with age in the study population, which was consistent with the majority of the previous studies [14,18,24] .…”
Section: Resultssupporting
confidence: 92%
“…In a study examining 155 eyes, female adults had a thinner central corneal thickness, but the axial length, anterior chamber depth, lens thickness, and white-to-white distance were not significantly different between sexes. 17 Conversely, other studies have demonstrated that males tend to have larger morphometric eye parameters. In one study, sex-specific biometric differences in children were examined by analyzing 64 eyes of 64 adolescents from 32 sets of twins.…”
mentioning
confidence: 94%
“…For example, the single-nucleotide polymorphisms (SNPs, rs1401999) in the ABCC5 gene contribute to being associated with both anterior chamber depth (ACD) ( 3 ), and rs4148568 might be associated with the axial length (AL), carriage of high-risk rs4148568 genetic variants is associated with making the AL longer in northern Chinese people ( 4 ). Additionally, ocular biometric measurements are associated with demographic, environmental, and lifestyle factors such as age, gender, and diet ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%